FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PADA REMAJA DI KOTA DEPOK TAHUN 2021 - Dewi Aprilia Setyawati (2022)
Poor sleep quality will cause adverse effects on health. One of age groups that often have poor sleep quality is adolescents because of physiology, psychology, and social changes that happened during this time. The aim of this study was to determine factors associated with sleep quality among adolescents in Depok. This study used cross-sectional study design. A total of 254 adolescents from 3 different high schools located in Depok were recruited as samples by using a cluster random sampling technique. Variables studied are sex, smoking status, health status, coffee consumption, stress, smartphone use and physical activity. The research instruments used were online questionnaire consisted of PSQI, PSS-10, SAS-SV, and IPAQ-sf. Data were analysed using Chi-Square Test and Multiple Regression Test. Based on the results of multivariate analysis, the variable that has the greatest influence on sleep quality is high stress level. Adolescents with high stress level have a 9 times risk of having poor sleep quality compared to adolescents with low stress level (95% CI 1,83-45,80). Also, adolescents with excessive smartphone use have a 2 times risk of having poor sleep quality compared to adolescents with normal smartphone use (95% CI 1,11 - 4,24). Adolescents were recommended to manage their stress and stop using smartphone 30 minutes before sleep.